Comparison of the external morphology of Rhipicephalus sanguineus (Latreille, 1806) (Acari : Ixodidae) ticks from Brazil and Argentina - de Oliveira, P. R.; Bechara, G. H.; Denardi, S. E.; Saito, K. C.; Nunes, E. T.; Szabo, MPJ; Mathias, Maria Izabel Camargo [UNESP] (Elsevier B.V., 2005)
In the present study the external morphology of semi-engorged Rhipicephalus sanguineus females ticks from Brazil and Argentina were compared by scanning electron microscopy. Many differences were detected among the R. sanguineus collected at the two localities, such as body size, shape of the genital pore, and morphology of the sensory structures. All these characteristics are fundamental for the diagnosis of species of the genus Rhipicephalus and thus indicate the need for further comparisons and, the taxonomical revision of this species of tick in the Neotropics. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Ixodidae; external morphology; Brazil; Argentina